Trichilemmal Carcinoma of the Thigh - Rakoczy, Anna; Reweda-Kwiatkowski, Konrad; Kowalik, Krzysztof; Parafiniuk, Mirosław; Gruszczyńska, Anna; Waloryszak, Arkadiusz; Grabarek, Jerzy; Pękala, Marek; Modrzejewski, Andrzej (Dermatology Review/Przegląd Dermatologiczny, 2025)
The authors report a rare case of trichilemmal carcinoma, a neoplasm arising from the outer root sheath of the hair follicle, localized in the thigh region. The article details the clinical history of a 71-year-old patient with a tumor that had progressively enlarged over several years, ultimately presenting with significant size, bleeding, and malodor. Surgical excision was performed, and histopathological analysis confirmed the diagnosis of trichilemmal carcinoma with clear surgical margins, indicating a complete and radical resection. Histopathological examination following surgical excision confirmed the diagnosis of trichilemmal carcinoma and revealed clear surgical margins, supporting the radical nature of the procedure. The authors also review the literature on trichilemmal carcinoma, discussing the risk factors, diagnosis, and treatment of this tumor. They emphasize that, while trichilemmal carcinoma typically follows a relatively benign course and recurrence is rare after complete resection, metastases may require chemotherapy. The article highlights the challenge of standardizing treatment due to the lack of clear guidelines on chemotherapy for metastatic cases, partly resulting from the limited number of cases available in the literature. The authors’ conclusions underscore the necessity of close follow-up for patients post-surgery due to the risk of recurrence, which is especially important for optimizing long-term disease management and improving patient prognosis.